Publication Preview Source FREE TIME RETIREMENT VERSUS HEALTH PHYSICAL FITNESS WHAT PLANS TO ADOPT A HEALTHIER LIFESTYLE! CASE UNIVERSITY SECURITY SECTORS WORKERS - Hamzaoui, Hakim; Messaliti, Lakhdar; Zerf, Mohammed; Bengoua, Ali (https://www.researchgate.net/publication/303372493_, 2016)
The interplay between productivity and retirement life is central to many core issues regarding pensions and re-tirement According to recent research published in the journal Epidemiology, (Q. Asthon Acton, PhD, 2011). Whereas (Lisa F. Berkman, et al, 2014) confirm by Gallo and colleagues that worker approach retirement, may have extensive phys-ical and mental health consequences. Where the free time as physical inactivity contributes to substantially and the global burden of disease. Based on background that the Retirement is a risk life stage due to the change in lifestyle. Our aims in this study are to examine these Impact on university security sectors workers. Where our hypotheses come based on the free time Retirement and the ab-sence of leisure activities (Mo Wang, 2012). Since the limit of the study Our assuming was based on the heartbeat, time, efforts, formula Power (Watts), the sugar level in blood, Maximum Heart Rate and Blood pressure whereas the samples were selected by the intentional man-ner included 14 participants in good medical health with good habits (no-smoking and no-drinkers) their mean age≤ 53,21 years working in the security sector of university 7 retirees in the previous year and 7 awaiting their retirement. Based on the applied statistics our findings showed that retirement is associated with negative changes in lifestyle security sectors which increased risk for high blood pressure and the deteriorating physical health level. Whereas Promot-ing healthy lifestyles is a vital message government responsibility to their community (Great Britain. Parliament. House of Lords, 2006) to increase their social activities. (Dianne Hales, 2014)
Keywords: Free Time Retirement, Health Physical Fitness, University Security Sector Workers